Profiling neurotransmitter-evoked glial responses by RNA-sequencing analysis - Wang, Mengxiao; Ho, Margaret S. (Frontiers in Neural Circuits, 2023)
Fundamental properties of neurons and glia are distinctively different. Neurons are excitable cells that transmit information, whereas glia have long been considered as passive bystanders. Recently, the concept of tripartite synapse is proposed that glia are structurally and functionally incorporated into the synapse, the basic unit of information processing in the brains. It has then become intriguing how glia actively communicate with the presynaptic and postsynaptic compartments to influence the signal transmission. Here we present a thorough analysis at the transcriptional level on how glia respond to different types of neurotransmitters. Adult fly glia were purified from brains incubated with different types of neurotransmitters ex vivo. Subsequent RNAsequencing analyses reveal distinct and overlapping patterns for these transcriptomes. Whereas Acetylcholine (ACh) and Glutamate (Glu) more vigorously activate glial gene expression, GABA retains its inhibitory effect. All neurotransmitters fail to trigger a significant change in the expression of their synthesis enzymes, yet Glu triggers increased expression of neurotransmitter receptors including its own and nAChRs. Expressions of transporters for GABA and Glutamate are under diverse controls from DA, GABA, and Glu, suggesting that the evoked intracellular pathways by these neurotransmitters are interconnected. Furthermore, changes in the expression of genes involved in calcium signaling also functionally predict the change in the glial activity. Finally, neurotransmitters also trigger a general metabolic suppression in glia except the DA, which upregulates a number of genes involved in transporting nutrients and amino acids. Our findings fundamentally dissect the transcriptional change in glia facing neuronal challenges; these results provide insights on how glia and neurons crosstalk in a synaptic context and underlie the mechanism of brain function and behavior.